Poly(N-vinyl-2-pyrrolidone-maleic anhydride-styrene) grafted terpolymer: Synthesis, characterization, and bactericidal property evaluation against E. coli and S. epidermidis. Issue 7 (3rd July 2017) - Ajithkumar, M. P.; Yashoda, M. P.; Prasannakumar, S.; Sruth, T. V.; Sameer Kumar, V. B.
ABSTRACT: Poly(N-vinyl-2-pyrrolidone-maleic anhydride-styrene) terpolymer was prepared using AIBN initiator with acetone as solvent. The terpolymer was grafted with anti-bacterial agents para-aminobenzoic acid and 2, 4-dichlorophenol to introduce bactericidal activity to the terpolymer. The terpolymer and the grafted polymers were characterized by FTIR, 1 H-NMR, and 13 C-NMR spectroscopic methods. Thermal properties were determined by differential scanning calorimetric technique and thermogravimetric analysis. The glass transition temperature was found to be 111°C (terpolymer), 150°C (VMS-G-PABA) and 130°C (VMS-G-DCP). Terpolymer starts degradation at 288°C and grafted terpolymers at 104°C (VMS-G-PABA) and 129°C (VMS-G-DCP), respectively. The anti-bacterial activity of grafted terpolymers were evaluated by the shake flask method against gram positive and gram negative bacteria E. coli and S. epidermidis . The grafted terpolymers showed effective inhibition against both the bacteria, the minimum inhibition concentration was observed to be 75 µg/mL and 80 µg/mL for VMS-G-PABA and 50 µg/mL for VMS-G-DCP against E. coli and S. epidermidis, respectively. The new polymers showed 90% bacterial growth inhibition at 200 µg/mL.